Engineering properties of self-compacting concrete incorporating PET fibres and recycled fine concrete aggregates - Meriem Bayah; Farid Debieb; El-Hadj Kadri; Mohamed Bentchikou (Budownictwo i Architektura, 2024)
Concrete is currently the most frequently used material in the building sector due to its favourable properties. However, the proliferation of waste poses a significant environmental problem. Over the past three decades, researchers have explored the use of construction and demolition waste (CDW) as well as plastic waste as aggregates, binders, and fibres in construction materials. This approach has emerged as a notable solution to address environmental and economic challenges. The objective of this research is to assess the impact of polyethylene terephthalate fibres (PETF) on the behaviour of self-compacting concrete (SCC) with recycled fine concrete aggregates (RFCA). Natural fine aggregates (NFA) were used as a substitute for RFCA at different mass fractions (0–100%). Additionally, four volumetric fractions (Vf) of PETF (ranging from 0.3% to 1.2%) were added, and the findings revealed an improvement in the flexural strength and modulus of elasticity of the composite material obtained. However, as the Vf content of PET fibres and RFCA increased, the compressive strength decreased, negatively affecting water absorption by immersion and capillary water absorption. Using 100% RFCA and 1.2% PETF enhanced the modulus of elasticity and flexural strength of recycled self-compacting concrete (RSCC) by up to 25% and 9%, respectively.